Implementasi Multi-Authentication pada Smart Door Lock Berbasis ESP8266 - Lilik Widyawati; Husain Husain; Kurniadin Abdul Latif; L. Irvan Sastrawan (Sekawan Institut, 2026)
Home security has become a primary concern, where conventional lock systems have significant weaknesses such as risk of loss, ease of duplication, and inability for remote monitoring. This re-search develops a Smart Door Lock system based on ESP8266 and Blynk with a multi-sensor and multi-authentication approach to overcome these problems. The system integrates RFID RC522 and 4x4 keypad as two-factor authentication (2FA) that can be toggled as needed, equipped with IR MH-B sensor for forced entry detection, ESP32-CAM for visual documentation, and Blynk platform for remote management. The research uses the ADDIE method which includes analysis, design, development, implementation, and evaluation stages with Black Box Testing approach. Imple-mentation results show the system successfully functions with a success rate of 98.29% from 1,405 tests. Average RFID reading time 447.5ms, total access time 1.27 seconds, and Blynk notification delay 2.38 seconds, meeting the response target of < 3 seconds. The 2FA mechanism proved effec-tive with 100% validation accuracy, toggle mode functions perfectly with EEPROM persistence. Remote management features via Blynk achieved 100% reliability for adding and removing RFID cards, changing passwords, and remote control. The IR sensor successfully distinguished legal and forced openings with 97.5% accuracy. ESP32-CAM integrated perfectly with automatic trigger via REST API for visual documentation to Telegram. The system is considered feasible as a modern, secure, and easy-to-operate home security solution.